2017
DOI: 10.1186/s12943-017-0665-0
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of adenosine A2A receptor enhances CD8+ T cells response and decreases regulatory T cells in head and neck squamous cell carcinoma

Abstract: BackgroundCancer immunotherapy offers a promising approach in cancer treatment. The adenosine A2A receptor (A2AR) could protect cancerous tissues from immune clearance via inhibiting T cells response. To date, the role of A2AR in head and neck squamous cell carcinoma (HNSCC) has not been investigated. Here, we sought to explore the expression and immunotherapeutic value of A2AR blockade in HNSCC.MethodsThe expression of A2AR was evaluated by immunostaining in 43 normal mucosae, 48 dysplasia and 165 primary HNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(138 citation statements)
references
References 58 publications
(79 reference statements)
3
120
0
4
Order By: Relevance
“…We showed that adenosine inhibited CD8 + T cell chemotaxis, and this effect was enhanced in cells from HNSCC patients. This is consistent with immunohistochemical data of various solid tumors showing an inverse correlation between CD73 in the tumor and the infiltration of CD8 + TILs (4650). The advantage of the studies we have performed here over the correlative studies in tissue samples is that we have used a collagen-rich 3D microenvironment where we have full control over the experimental conditions used, while in vivo, the TME is a complex mixture of metabolic and waste products and tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…We showed that adenosine inhibited CD8 + T cell chemotaxis, and this effect was enhanced in cells from HNSCC patients. This is consistent with immunohistochemical data of various solid tumors showing an inverse correlation between CD73 in the tumor and the infiltration of CD8 + TILs (4650). The advantage of the studies we have performed here over the correlative studies in tissue samples is that we have used a collagen-rich 3D microenvironment where we have full control over the experimental conditions used, while in vivo, the TME is a complex mixture of metabolic and waste products and tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Adenosine, a purine metabolite present at high concentration in the TME, also acts by limiting the activity of protective immune infiltrates, including NK cells, and enhancing that of Tregs and MDSCs (128). Adenosine accumulated in the TME by CD39 and CD73, causing inhibition of tumor-infiltrating NK cells by binding to the purinergic adenosine A 2A receptor expressed on cell surface (129)(130)(131)(132)(133). Reduction of adenosine by blocking both CD73 and the A 2A receptor was shown to affect tumor growth and promote recruitment of tumor-infiltrating NK cells (134).…”
Section: Immunosuppressive Properties Of the Tme On Nk Cellsmentioning
confidence: 99%
“…The inhibition role of ADO in antitumor T cells is mediated by A2AR and A2BR. Pharmacological blockade of A2AR not only enhances CD8 + T cells anti-tumor response but also reduces the population of Tregs [62]. A2AR antagonist or silence by siRNA could improve the inhibition of tumor growth, destruction of metastases and prevention of neovascularization by anti-tumor T cells [63].…”
Section: Ado and T Cellsmentioning
confidence: 99%